MEANS OF EXPRESSING DISAGREEMENT IN LINGUOCULTUROLOGICAL APPROACH (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
The concept of disagreement, as well as its antonym consent, originated in philosophy in  antiquity. This term was actively used by such ancient thinkers as  Socrates and Plato. They used it in their works, analyzing completely  new approaches to human existence. For ancient thinkers, "disagreement"  is a way to negate previous theories.  With the phenomenon known as the "linguistic turn," when there was awareness of the priority of language and an active study of dialogic speech, the topic of disagreement started to be actively investigated in linguistics. The speech act of disapproval was typically examined in publications alongside the speech act of consent [64,14-15].  "The speech act of a negative reaction is a reactive act expressing  the speaker's negative attitude to the interlocutor's action or statement, which is an informative, evaluative or  imperative statement with various emotional shades and  has a certain embodiment in speech".